MODELING OF TEXT RECOGNITION IN IMAGES - Karimova Mavzuna (Journals Park Publishing, 2022)
We distinguish between perceptual and physical texture differences: the former differences are those perceived by humans, while the latter, on which we concentrate, are those defined by differences in the processes that create the texture in the scene. The task of texture segmentation is to identify image curves that separate different textures. To segment textured images, one must first be able to discriminate textures. A segmentation algorithm performs texture-discrimination tests at densely spaced image positions, then interprets the results to localize edges. This article focuses on the first stage, texture discrimination.
Keywords: Images, textures, segment, while the latter, segmentation, modeling